2016
DOI: 10.1039/c6tb01710j
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrrole-coated poly(l-lactic acid-co-ε-caprolactone)/silk fibroin nanofibrous membranes promoting neural cell proliferation and differentiation with electrical stimulation

Abstract: Conductive nanofiber membranes were developed by coating Ppy on PLCL/SF nanofibers via in situ oxidative polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 31 publications
4
88
0
Order By: Relevance
“…The incorporation of conductive polymer elements for neuronal tissue engineering has become quite common. Sun et al prepared an electrospun poly( l ‐lactic acid‐ co ‐e‐caprolactone)/silk fibroin (PLCL/SF) coated with in situ polymerized PPy nanoparticles. Addition of PPy improved scaffold hydrophilicity and conductivity up to 0.1 mS cm −1 .…”
Section: Conductive Scaffolds For Neuronal Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of conductive polymer elements for neuronal tissue engineering has become quite common. Sun et al prepared an electrospun poly( l ‐lactic acid‐ co ‐e‐caprolactone)/silk fibroin (PLCL/SF) coated with in situ polymerized PPy nanoparticles. Addition of PPy improved scaffold hydrophilicity and conductivity up to 0.1 mS cm −1 .…”
Section: Conductive Scaffolds For Neuronal Tissue Engineeringmentioning
confidence: 99%
“…These facts demonstrate the necessity of the conductive element in the system to augment neuronal cell development via electrical stimulation. Further emphasizing the promise of conductive polymers for peripheral nerve treatment, Sun et al performed follow up experiments to their 2016 study by using their PLCL/SF/PPy scaffold in vivo . Results of rat sciatic nerve treatment showed matching results with the gold standard autograft in most metrics, save for slightly diminished axonal diameter and myelin thickness, in which the nondoped control paled in comparison.…”
Section: Conductive Scaffolds For Neuronal Tissue Engineeringmentioning
confidence: 99%
“…Nevertheless, the cells displayed better adhesion and spreading on the substrates with higher conductivity (>10 −4 S cm −1 ). To analyze the influence of conductivity on the differentiation of PC12 cells, NGF (100 ng mL −1 ) was introduced into the cell culture system . Under the condition of adding growth factor, some cells are no longer in the state of proliferation after 4 days of culture, and the cells show differentiation behavior and grow synapses.…”
Section: Resultsmentioning
confidence: 99%
“…Sun et al suggested that ES could promote SC proliferation according to the membranes coated with PPY. 24,39,40 However, in other studies, Abigail N. Koppes et al suggested that ES had no signicant inuence on SC proliferation. 8 Therefore, there was discrepancy on the effect of ES on SC proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…Most importantly, the resistivity of the conductive scaffolds consisting of these polymer materials is in the range of 1000-40 000 U cm. [22][23][24] Therefore, a larger ES intensity may be required, which might damage the neural cells and tissues. An ideal conductive scaffold should provide not only electrical properties but also biocompatibility cues for guiding neural cell growth.…”
Section: Introductionmentioning
confidence: 99%